Growth Forecasts, Belief Manipulation and Capital Markets - Frederik Lundtofte; Patrick Leoni (Lund University, School of Economics and Management, Department of Economics, 2012)
We analyze how a benevolent, privately-informed government agency would optimally release information about the economy's growth rate when the agents hold heterogeneous beliefs. We model two types of agents: "trusting" and "distrustful." The former has a prior that is identical to that of the government agency, whereas the latter has a prior that differs from that of the government agency. We identify both "revealing" and "nonrevealing" equilibria and demonstrate that the "nonrevealing" equilibria can dominate the "revealing" equilibria in terms of ex-post social welfare.
Keywords: D83; G11; G12; 330; Social welfare; information; forecasting; asset pricing; heterogeneous beliefs